Zwitterionic iodonium species afford halogen bond-based porous organic frameworks; Chemical Science; Vol. 13, iss. 19 - Soldatova N. S. Nataliya Sergeevna; Postnikov P. S. Pavel Sergeevich; Ivanov D. M. Daniil Mikhaylovich; Semyonov O. V. Oleg Vladimirovich; Kukurina O. S. Olga Sergeevna; Guselnikova O. A. Olga Andreevna; Yamauchi Yu. Yusuke; Wirth T. Thomas; Zhdankin V. V. Viktor Vladimirovich; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Rosa M. G. Maria Gomila; Frontera A. Antonio; et al. (2022, 2022)
Title screen